Relevance of Sample Size Determination in Medical Research - Sathian, Brijesh; Sreedharan, Jayadevan; Baboo, Suresh N; Sharan, Krishna; Abhilash, E S; Rajesh, E (Nepal Journal of Epidemiology, 2010)
Sample size determination is one of the central tenets of medical research. If the sample size is inadequate, then the study will fail to detect a real difference between the effects of two clinical approaches. On the contrary, if the sample size is larger than what is needed, the study will become cumbersome and ethically prohibitive. Apart from this, the study will become expensive, time consuming and will have no added advantages. A study which needs a large sample size to prove any significant difference in two treatments must ensure the appropriate sample size. It is better to terminate such a study when the required sample size cannot be attained so that the funds and manpower can be conserved. When dealing with multiple sub-groups in a population the sample size should be increased the adequate level for each sub-group. To ensure the reliability of final comparison of the result, the significant level and power must be fixed before the sample size determination. Sample size determination is very important and always a difficult process to handle. It requires the collaboration of a specialist who has good scientific knowledge in the art and practice of medical statistics. A few suggestions are made in this paper regarding the methods to determine an optimum sample size in descriptive and analytical studies. Key Words: Sample size; Power analysis; Medical research DOI: 10.3126/nje.v1i1.4100 Nepal Journal of Epidemiology 2010;1 (1):4-10